2021
DOI: 10.1002/adfm.202101452
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Modification of SIS Membrane with Chimeric Peptides to Promote Its Antibacterial, Osteogenic, and Healing‐Promoting Abilities for Applying to GBR

Abstract: Guided bone regeneration (GBR) technology is the most widely used and stable method for bone defect repair. However, infectious bone defect limits the application of this technique. Herein, a small intestinal submucosa (SIS) membrane modified by chimeric peptides as a new type of GBR membrane is developed for efficacious tissue regeneration. Based on the main components of SIS membrane are I and III collagen, collagen binding peptides TKKTLRT and KELNLVY sequences are used to construct chimeric peptides with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Bone defects caused by trauma, fracture, osteomyelitis, or bone tumor resection are often accompanied by infection, leading to poor clinical prognosis. [162][163][164][165] MPNs combine the specific functions of metal ions and polyphenol ligands, exhibiting unique advantages that are tailored to the desired properties of orthopedic biomaterials. Natural polyphenols contain plenty [159] Copyright 2021, Elsevier.…”
Section: Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone defects caused by trauma, fracture, osteomyelitis, or bone tumor resection are often accompanied by infection, leading to poor clinical prognosis. [162][163][164][165] MPNs combine the specific functions of metal ions and polyphenol ligands, exhibiting unique advantages that are tailored to the desired properties of orthopedic biomaterials. Natural polyphenols contain plenty [159] Copyright 2021, Elsevier.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Bone defects caused by trauma, fracture, osteomyelitis, or bone tumor resection are often accompanied by infection, leading to poor clinical prognosis. [ 162–165 ] MPNs combine the specific functions of metal ions and polyphenol ligands, exhibiting unique advantages that are tailored to the desired properties of orthopedic biomaterials. Natural polyphenols contain plenty phenolic hydroxyl groups providing tissue adhesive, antioxidant, and anti‐inflammatory properties in addition to metal ions chelating ability, and some specific polyphenols have antimicrobial properties themselves.…”
Section: Antibacterial Application Of Mpns‐based Biomaterialsmentioning
confidence: 99%
“…Masson's staining ( Fig. 8 b) was used to identity the collagen in bone matrix to observe the activity of osteogenesis [ 62 ]. The blue staining area (collagen) was larger in p 1&2 SIS-CA/Exs and p 3&4 SIS-CA/Exs groups than that in SIS-CA and SIS-CA/Exs groups, indicating that there is a lot of new bone.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that metallic implants have disadvantages, such as foreign body reactions with surrounding tissues, infection, and inflammatory reactions caused by micro-organisms in the oral cavity after implantation [ 5 , 6 ]. In recent research on GBR membranes, prevention of bacterial infection, wound healing, and induction of bone regeneration after GBR surgery were found to be very important factors for the success of the surgery [ 7 ]. Therefore, it was assumed that developing a biocompatible implant with antimicrobial properties against representative micro-organisms and general pathogens present in the oral cavity can increase the success rate of implantation in the dental or orthopedic clinical field.…”
Section: Introductionmentioning
confidence: 99%